EXPLORING THE COMPLEX RELATIONSHIP BETWEEN IDEAL BODY WEIGHT AND LIFE EXPECTANCY: IN-DEPTH ANALYSIS OF HEALTH, GENETICS, AND SOCIOECONOMIC FACTORS - Fadli Fadli; Imam Hanafi; Era Purike; Rahmah Fitria; Emdat Suprayitno (ADISAM Publisher, 2024)
This study delves into the intricate relationship between ideal body weight and life expectancy by analyzing the factors of health, genetics, and socioeconomic conditions. The research background is rooted in the growing awareness of the significance of health and improved quality of life. The primary aim is to understand how ideal body weight can influence an individual's life expectancy while identifying the impacts of health, genetics, and socioeconomic factors within this relationship. The study employs an interdisciplinary approach, combining health, genetics, and socioeconomic data. The analysis findings will uncover the complex link between ideal body weight and life expectancy. The research will also discuss the effects of health factors like dietary patterns and physical activity, as well as the role of genetics in determining longevity. Additionally, the study will outline the influence of socioeconomic factors such as education and income on life expectancy. By delving into this relationship, the research can offer valuable insights for developing public health policies and better understanding how individuals can achieve longer and higher-quality lives through appropriate weight management while considering the involved health, genetics, and socioeconomic factors.